Hate Speech Crimes Through Social Media as Cyber Crimes - Donson Sijabat; Wahab Aznul Hidaya; A. Sakti R.S. Rakia (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the application of criminal law in addressing hate speech on social media and to identify the effectiveness of Law Number 11 of 2008 on Electronic Information and Transactions. This study uses a normative juridical approach with qualitative methods, in which data is collected through the analysis of legal documents such as the ITE Law, the Criminal Code, and case jurisprudence from 2020-2023, as well as a literature study of scientific journals, research reports, and comparative data from other countries. The novelty of this research lies in its integrative approach, which combines normative legal analysis with a cybercriminology perspective, resulting in a comprehensive model for handling digital hate speech. Unlike previous studies, which tended to be partial, this study presents a new theoretical framework that explains the unique characteristics of hate speech as a cybercrime and proposes transformative strategies based on the synergy of regulation, technology, and community participation. The results of the study show that the application of criminal law in addressing hate speech on social media faces complex challenges, especially those related to the viral and cross-jurisdictional nature of digital content. Although Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) has provided a legal basis, its effectiveness is still hampered by several factors, including difficulties in proving cases, limited understanding among law enforcement officials, and the rapid dynamics of technological developments. In conclusion, handling hate speech as a cybercrime requires regulatory reform, increased law enforcement capacity, and public education. Prevention efforts should focus on strengthening digital literacy, while law enforcement needs to be optimized through the application of technology and international cooperation.